PENINGKATAN LITERASI DAN NUMERASI PADA SISWA SISWI SDN 02 CIHERANG - Hardjo, Ayra Diputera; Effendi, Absarani Maharani; Edang, Ignasius Alfon Hanjuk; Rajasa, Daud Angga; Arisandi, Desi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Mastery of literacy and numeracy skills is important for everyday life, not just in school. Literacy is a general term that refers to a set of individual abilities and skills in reading, writing, speaking and solving problems at a certain level of expertise needed in everyday life, and numeracy is a special ability in counting, and knowledge of using various kinds of symbols related to basic mathematics to solve practical problems so that numerical abilities affect students' ability to understand and solve problems related to numbers. This problem is the background for the activities of Group 2 KKN-T students to carry out a work program to improve students' literacy and numeracy skills. This program is aimed at grade 1 and grade 4 students considering that grade 1 and grade 4 students have changed the curriculum from the 2013 curriculum (K-13) to the 2021 curriculum, namely the Merdeka Curriculum. Grade 1 and grade 4 students were selected for the implementation of the Merdeka curriculum, before it was implemented at all grade levels. The purpose of this program is to hone and strengthen students' literacy and numeracy knowledge and skills in interpreting numbers, and enriching vocabulary. The activities carried out are by giving practice problems in the form of stories and conducting questions and answers to increase interaction between students and teaching staff. Based on the results of the assessment of students, it is known that this program received a good response from students. The results of this activity became a benchmark for creating teaching materials that were submitted to teachers to help improve literacy and numeracy skills, especially for grade 1 and grade 4 students, as well as for all students of State Elementary School 02 Ciherang. ABSTRAK Penguasaan kemampuan literasi dan numerasi adalah hal yang penting bagi kehidupan sehari – hari, bukan hanya dalam lingkup sekolah saja. Literasi adalah istilah umum yang merujuk kepada serangkaian kemampuan dan keterampilan individu dalam membaca, menulis, berbicara dan memecahkan masalah pada tingkat keahlian tertentu yang diperlukan dalam kehidupan sehari-hari, dan numerasi adalah kemampuan khusus dalam hitung menghitung, dan pengetahuan menggunakan berbagai macam simbol terkait matematika dasar guna memecahkan masalah praktis sehingga kemampuan numerik mempengaruhi kemampuan siswa dalam memahami dan menyelesaikan soal yang berhubungan dengan angka. Hal ini melatar belakangi kegiatan mahasiswa Kelompok 2 KKN-T untuk melakukan program kerja peningkatan kemampuan literasi dan numerasi siswa. Program ini ditujukan kepada siswa kelas 1 dan kelas 4 mengingat para siswa kelas 1 dan kelas 4 mendapati pergantian kurikulum yang semula kurikulum 2013 (K-13) menjadi kurikulum 2021 yaitu Kurikulum Merdeka. Siswa kelas 1 dan kelas 4 dipilih untuk implementasi kurikulum Merdeka, sebelum diimplementasikan di semua tingkatan kelas. Tujuan dari program ini adalah untuk mengasah serta menguatkan pengetahuan dan keterampilan literasi dan numerasi siswa dalam menginterprestasikan angka, serta memperkaya perbendaharaan kosa kata. Kegiatan yang dilakukan adalah dengan memberi latihan soal dalam bentuk cerita maupun melakukan tanya jawab untuk meningkatkan interaksi antara siswa dengan tenaga pengajar. Berdasarkan hasil penilaian terhadap siswa, diketahui bahwa program ini mendapat respon yang baik dari para peserta didik. Hasil dari kegiatan ini menjadi tolak ukur untuk membuat materi ajar yang diserahkan kepada guru untuk membantu meningkatkan kemampuan literasi dan numerasi, khususnya pada siswa kelas 1 dan kelas 4, maupun untuk seluruh siswa Sekolah Dasar Negeri 02 Ciherang.